Dependability assessment by simulation of a dynamic system with different modes of ageing - Pérez Castañeda, Gabriel Antonio; Aubry, Jean Fran í§ois; Brinzei, Nicolae (Rev. Téc. Fac. Ing. Univ. Zulia, 2012)
The concept of dynamic reliability aims to take into account the interactions between the dynamic and deterministic functional behavior of the system and the stochastic dysfunctional behavior of its components. Some problems must be taken into account in the dynamic reliability: (i) the dynamic interactions between the physical parameters (usually represented by the continuous variables) and the nominal or dysfunctional behavior of the components (usually represented by the occurrence of events), (ii) the instant and the order of the events occurrence, including failures, (iii) the modes of ageing of the multiple components according to the system state. The traditional tools of the reliability can not be applied effectively to solve these problems because they assume an invariant structure in time for the system. This paper presents the reliability assessment of a dynamic system in which there are reconfigurations involving various modes of ageing for some components (changing laws, changing the parameters of laws etc.). The performance indices of the system, such as the reliability, the availability and the maintainability, are determined by Monte Carlo simulation.